Considerations Concerning Mosaism in Carlist Romania (1938-1940) - Aurelian CHISTOL (Annals: Series on History and Archaeology (Academy of Romanian Scientists))
The Carlist coup d' tat of February 10, 1938 was intended to be the beginning of a New Romania, monarchical, nationalist, rediscovering traditions and respect for work and social harmony. Promising a far-reaching reform of state institutions and the regeneration of the entire nation, which was to rally around the sovereign to protect the country from the dangers that lurked at every turn, the New Regime also paid special attention to the delicate question of its relations with the various religious denominations in Romania. The relationship between the state and the Mosaic culture proved to be extremely interesting, characterized by the concern on both sides not to cross a "red line" and not to violate constitutional provisions. The mutual respect formally expressed in public did not, however, rule out moments of tension, which have always been overcome without escalating the latent conflict between the two sides. The analysis of the relations between the Carlist regime and the representatives of the Mosaic cult is not only a topical historical subject, but also an opportunity for reflection for the servants of Clio, contributing to a better understanding of the dramatic moments Romania went through between 1938-1940.